Performative images : a philosophy of video art technology in France - Nony, Anaïs (Amsterdam University Press, 2023)
Performative Images draws upon the work of video artists and activists in France between the 1970s and the early 2020s and focuses on significant practices with technology. Video art and video activism are analysed together in the book to revaluate key concepts in media studies and foreground a performative approach to the theory of image technology. The book engages works in visual culture, performance studies, digital studies, critical race theory, and feminist methodologies to account for the changes brought about by video technology in social and psychic life. Performative Images is about art and activists' engagement in video technology-an engagement that unsettles the hegemonic narrative of dominant media, as well as the apparently politically neutral dimension of communication technology. In this book, the author explores how video-image technology shapes our psychic and social environments from an art historiographical perspective. We know media technology is dramatically shaping our political and epistemological landscape: this book foregrounds the emergence of performative video images as a key factor in the revaluation of culture and politics.
Introduction: Video: Between Technology and Performance Chapter 1: The Volume-Image of Video Technology Chapter 2: Zones of Modulation: Video as a Space-Critical Medium Chapter 3: Programmed Life and Racialized Technesis Chapter 4: Video and the Technical Milieu of Desire Conclusion: Performative Images as Objects of Philosophical Inquiry Artworks cited Index Acknowledgments
Keywords: Video art -- France.; Art and technology -- France.; Art vidéo -- France.; Art et technologie -- France.; Film theory and criticism.; Media studies.; ART / Film & Video.; ART / Performance.; SOCIAL SCIENCE / Media Studies.; Performance art.; Film history, theory or criticism.; Film, Media, and Communication; FMC; Art and Material Culture; ART & MAT; Film Studies; FILM; Media Studies; MEDIA; Thierry Kuntzel, Video Art, Performance Studies, Media Studies, France; Electronic books.